2005
DOI: 10.1002/cphc.200400588
|View full text |Cite
|
Sign up to set email alerts
|

Car–Parrinello Molecular Dynamics Study of DCl Hydrate Crystals

Abstract: Three DCl hydrates have been studied using Car-Parrinello (CP) molecular dynamics. The structural results at low temperatures (T<350 K) agree with experiment and previously published CP results. The monohydrate has been shown to be built from D3O+ and Cl- ions. The dihydrate is built exclusively from D5O2+ and Cl- ions. The trihydrate consists of D2O, D5O2+, and Cl- ions. Thus, the DCl hydrates are excellent systems for studying ideal D3O+ and D5O2+ ions. The data from these ideal structures can be compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…The low-energy minima structures of HCl(H 2 O) n clusters with n ≤ 6 have been explored using different electronic structure methods. In the past decade, both Car–Parrinello (CPMD) and Born–Oppenheimer (BOMD) molecular dynamics simulations were carried for HCl(H 2 O) n clusters with n ≤ 6 and their deuterated analogs. ,,, These ab initio molecular dynamics (AIMD) simulations show that the relative stability of different HCl(H 2 O) 6 isomers is significantly affected by temperature . CPMD simulations carried out for DCl(D 2 O) n with n = 1–6 were also used to determine the relationships between energies, structures, and spectroscopic features .…”
Section: Introductionmentioning
confidence: 99%
“…The low-energy minima structures of HCl(H 2 O) n clusters with n ≤ 6 have been explored using different electronic structure methods. In the past decade, both Car–Parrinello (CPMD) and Born–Oppenheimer (BOMD) molecular dynamics simulations were carried for HCl(H 2 O) n clusters with n ≤ 6 and their deuterated analogs. ,,, These ab initio molecular dynamics (AIMD) simulations show that the relative stability of different HCl(H 2 O) 6 isomers is significantly affected by temperature . CPMD simulations carried out for DCl(D 2 O) n with n = 1–6 were also used to determine the relationships between energies, structures, and spectroscopic features .…”
Section: Introductionmentioning
confidence: 99%
“…Past computational studies of the HCl hydrate systems included modeling of the monohydrate, dihydrate, and trihydrate using Car−Parrinello molecular dynamics (CPMD) and Car−Parrinello path integral molecular dynamics CP-PIMD and another more recent CPMD study of these systems …”
Section: Introductionmentioning
confidence: 99%
“…We use the HCl–water cluster system to illustrate and validate the present first-order quantum vibration perturbation (QVP1) approach because strong hydrogen-bonding and dispersion interactions are important and because it has been extensively investigated experimentally and theoretically. Although this appears to be a small test case, it is in fact challenging because of the strong bond-dissociation character in the oscillator mode. We emphasize that the QVP1 method is equally efficient for condensed-phase simulations as in a combined QM/MM approach .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Havenith and co-workers confirmed that the broad band at 2675 cm –1 is due to the dissociated cluster, H 3 O + (H 2 O) 3 Cl – . On the theoretical side, Born–Oppenheimer molecular dynamics (BOMD) simulations with DFT-based potentials have been used to mode HCl­(H 2 O) n ( n = 1–4) clusters. ,− ,, Marx and co-workers obtained the IR spectra of the HCl–water clusters using the BLYP density functional. A sequential solvation process was proposed to account for the HCl dissociation mechanism, involving the interplay of quantum tunneling and thermal fluctuations from path integral simulations. ,, Employing a semiempirical PM3-MAIS potential, Lin and Paesani extended the investigation to larger clusters up to n = 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation